2022
DOI: 10.1039/d2nj00061j
|View full text |Cite
|
Sign up to set email alerts
|

Impact of positive charge and ring-size on the interactions of calixarenes with DNA, RNA and nucleotides

Abstract: Comparison of various calix[6]arene and calix[4]arene derivatives revealed that only analogues bearing permanent positive charge non-covalently bind to ds-DNA and ds-RNA, by insertion into DNA minor groove or RNA major...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 43 publications
(106 reference statements)
0
10
0
Order By: Relevance
“…aThe best fit of experimental data was obtained for 1 : 1 stoichiometry of dye/NMP complex or for DNA/RNA by processing of titration data by means of Scatchard equation gave values of ratio n [bound dye]/[DNA/RNA] = 0.1 and 0.2, for easier comparison all log K values were re-calculated for fixed n = 0.2.bΔInt = Int(100% complex)/Int 0 .cPublished data. 9 For DNA/RNA log K values estimated from competition experiments.…”
Section: Resultsmentioning
confidence: 66%
See 3 more Smart Citations
“…aThe best fit of experimental data was obtained for 1 : 1 stoichiometry of dye/NMP complex or for DNA/RNA by processing of titration data by means of Scatchard equation gave values of ratio n [bound dye]/[DNA/RNA] = 0.1 and 0.2, for easier comparison all log K values were re-calculated for fixed n = 0.2.bΔInt = Int(100% complex)/Int 0 .cPublished data. 9 For DNA/RNA log K values estimated from competition experiments.…”
Section: Resultsmentioning
confidence: 66%
“…[5][6][7][8] Some of these systems were recently studied by us as possible candidates for DNA/RNA binding in a frame of a wider project oriented towards the research of DNA/RNA recognition by specially designed calixarene derivatives. 9,10 Development of new biomimetic systems capable of selective DNA/RNA binding is a subject of utmost importance for the development of new drugs, biosensors or tools for basic biochemical and biological studies. [11][12][13] The covalently linked pyrene functional group, belonging to a group of polycyclic aromatic hydrocarbons (PAH), is especially interesting to us due to its unique properties like intense blue emission, high uorescence quantum yield, long-lived singlet excited state, long emission lifetime (>100 ns), as well as its pronounced hydrophobicity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are many successful examples in the literature of using cationic calixarenes for DNA binding, compaction and even storage. For this can be used calixarene-amines [ 19 ], multicalixarene-amines [ 20 ], calixdendrimer-amines [ 21 ], calixarenes bearing guanidinium [ 22 , 23 , 24 ] or arginine [ 25 ] groups as well as calixarene-ammonium derivatives [ 26 , 27 , 28 ]. We have previously demonstrated that thiacalixarene derivatives in the 1,3-alternate configuration carrying two [ 29 ] or four [ 30 ] diethylenetriamine fragments in combination with triazole fragments effectively bind and compact DNA.…”
Section: Introductionmentioning
confidence: 99%